2017
DOI: 10.1002/oby.21858
|View full text |Cite
|
Sign up to set email alerts
|

The INTERGROWTH‐21st gestational weight gain standard and interpregnancy weight increase: A population‐based study of successive pregnancies

Abstract: ObjectiveTo link the INTERGROWTH‐21st gestational weight gain standard with the risks of excess maternal postpartum weight retention, approximated by women's weight change between successive pregnancies.MethodsA population‐based retrospective cohort study of 58,534 women delivering successive pregnancies in British Columbia, Canada (2000‐2015) was conducted. Pregnancy weight gain (kg) in the index pregnancy was converted into a gestational age‐standardized z‐score using the INTERGROWTH‐21st standard. Excess in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…The INTERGROWTH-21st Project developed standards in an international population of normal weight women by only including women with healthy pregnancies with good maternal and perinatal outcomes [ 7 ]. However, a recent study showed that the INTERGROWTH-21st standards do not seem to describe optimal weight gain patterns with respect to maternal postpartum weight retention and thus may still be descriptive [ 31 ]. We developed gestational weight gain reference charts by including all pregnant women that had all necessary information available for these analyses and compared with the charts obtained in a sample with good maternal and perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The INTERGROWTH-21st Project developed standards in an international population of normal weight women by only including women with healthy pregnancies with good maternal and perinatal outcomes [ 7 ]. However, a recent study showed that the INTERGROWTH-21st standards do not seem to describe optimal weight gain patterns with respect to maternal postpartum weight retention and thus may still be descriptive [ 31 ]. We developed gestational weight gain reference charts by including all pregnant women that had all necessary information available for these analyses and compared with the charts obtained in a sample with good maternal and perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, as Intergrowth 9 is a standard, and therefore has a prescriptive character, it is crucial to be cautious when using this reference due to gestational weight gain higher than P70 (excessive) already being associated with LGA. In the cohort study conducted by Hutcheon et al, 26 the authors assessed the risk of excessive maternal weight retention in the postpartum period involving weight change due to successive pregnancies, and found that between P51 and P84, risk of excessive weight retention also increased significantly. Jin et al 27 compared the ability to identify gestational diabetes in women with excessive GWG using three different methods (IOM, 2 Intergrowth 9 and a Chinese reference), and concluded that GWG higher than P84 according to Intergrowth 9 and the local Chinese reference, presented higher risk of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Among those who had not returned to pre-pregnancy weight by 12 months, the average weight retention remained relatively stable, at 3 ±5.7 kg (Phelan et al 2014). Over the course of several full-term pregnancies, each additional weight gain can thus accumulate to produce a significant metabolic burden (Hutcheon et al 2017) in the mother, with additional potential detrimental consequences for children born from subsequent pregnancies. It is thus important to understand as much as possible about factors that influence post-partum weight loss.…”
Section: Discussionmentioning
confidence: 99%